SEX SPECIFIC RISK FACTOR AWARENESS, COVERT MISOGYNY AND LONG-TERM CARDIOVASCULAR RISK MANAGEMENT: PILOT STUDY: Misogyny and Cardiovascular Risk: Pilot Study Results - Parapid, Biljana; Grujić, Žaklina; Bisenić, Ognjen; Djurović, Milica; Simić, Petar; Djikanović Tetiković, Bosiljka; Petrović, Sonja; Vuković Banjanac, Jovana; Simatović, Kristina; Djikić, Dijana; Petrović Djordjević, Ivana; Mladenović Marković, Ana; et al. (Medical Research, 2025)
INTRODUCTION: Health literacy is cornerstone of prevention, while sex specific prevention of cardiovascular disease – leading cause of death of women worldwide – remains less addressed and still matter of local cultural habits than guidelines directed management. METHODS: A validated multiple-choice questionnaire (MCQ) designed to both educate patients and help the healthcare team learn about their traditional and sex specific modern risk factors (RF) management, including opting for comprehensive personalized long term follow up (FU) was offered to all. RESULTS: Out of 130 patients hospitalized in our department (Jan 1, 2024 – Feb 24, 2024) who were offered to fill in the MCQ, 37.7% accepted, while 11.5% were excluded on ethical grounds. Women (49%) were older than men, had a more significant burden of traditional RF and possessed higher levels of knowledge and interest in RFs of both sexes, while men – especially those who declined to participate without a clear reason – even stated having no interest in their female relatives’ risk profiles. Men – unlike women – showed no particular interest in a personalized and tech-savvy options of FU, although they equally use hand-held devices. CONCLUSION: These results confirm results in a similar sample of only women conducted in the same setting a year ago, however, results in men where surprising for the hostility exhibited towards junior and mid-career women was absent when approached by a senior male member of the healthcare team, confirming misogyny needs to be actively suppressed. KEY WORDS: health literacy, heart disease, cardiovascular risk, sex specific risk factors, misogyny